A Defence of Statutory Property - Bullock, David AC (Victoria University of Wellington Law Review, 2017)
In "Statutory Property: Is it a Thing?" (2016) 47 VUWLR 411, Ben France-Hudson argues that tradable environmental allowances, like emissions units and fishing quota, are not "statutory property" and should instead simply be described and understood as "private property". In doing so, France-Hudson draws on a theory of private property as embodying norms of social obligation. This article defends the view of tradable environmental allowances as statutory property – though that term has a number of definitions – and argues that property in tradable environmental allowances can be explained by an orthodox understanding of the law of property.